ENHANCING PEDAGOGICAL COMPETENCIES IN PRE-SERVICE TEACHERS’ THROUGH MICROTEACHING: A QUALITATIVE STUDY - Eko Purwanti; Graciella Indrawati Suhargo (Indonesian Journal of Learning and Instruction, 2024)
Pedagogical competence is one of compulsory competencies required for teachers to perform their tasks professionally. To produce qualified teachers, many teacher training institutions provide courses that can help pre-service teachers build their pedagogical competences, such as Microteaching. However, not all pre-service teachers understand the importance of this course, and they barely take this course seriously. This research aimed to explore how Microteaching course can assist pre-service teachers build their pedagogical competences and explores its aspects that can be improved. Utilizing qualitative approach, six participants of preservice teachers of English language education department of Private University in Central Java were involved, and they were individually interviewed to collect the data. Microteaching course enables pre-service teachers build their pedagogical competences in that 1) it improves their lesson plan, 2) it provides them with teaching practice experiences, and 3) it gives opportunities for them to evaluate their teaching practices. In addition, Microteaching course enables the pre-service teachers to build their pedagogical competencies aspects, comprising 1)identifying students’ characteristics, 2) carrying out reflection, 3) understanding students’ learning, 4) developing students’ potentials, 5) building good communication skills, and 6) carrying out assessment and evaluation. As microteaching course enables pre-service teachers improve their pedagogical knowledge in many aspects, students of teacher training should take the course more seriously.